Association of established thyroid peroxidase autoantibody (TPOAb) genetic variants with Hashimoto's thyroiditis. (2nd October 2016) - Brčić, Luka; Barić, Ana; Gračan, Sanda; Brdar, Dubravka; Torlak Lovrić, Vesela; Vidan, Nikolina; Zemunik, Tatijana; Polašek, Ozren; Barbalić, Maja; Punda, Ante; Boraska Perica, Vesna
Abstract: Hashimoto's thyroiditis (HT) is the most common form of autoimmune thyroid diseases (AITD) characterized by progressive destruction of thyroid tissue that may lead to hypothyroidism. High thyroid autoantibodies against thyroid peroxidase (TPOAb) levels are present in 90% of patients with HT and serve as a clinical marker for the detection of early AITD/HT. The main aim of our study was to test whether recently identified genetic variants associated with TPOAb are also involved in HT development. A total of 504 unrelated individuals, including 200 patients with HT and 304 controls, were involved in this study. Diagnosis of HT cases was based on clinical examination, measurement of thyroid hormones (TSH and fT4) and antibodies (TgAb, TPOAb) and ultrasound examination. We selected and genotyped 14 known TPOAb-associated genetic variants. Case–control logistic regression model was used to test the association of selected genetic variants with HT. Additionally, we tested association of the same genetic variants with thyroid related quantitative traits (TPOAb levels, TgAb levels and thyroid gland volume) using linear regression. Three genetic variants showed nominal association with HT; rs10774625 in ATXN2 gene ( p  = 0.0149, OR = 0.73, CI = 0.56–0.94), rs7171171 near RASGRP1 gene ( p  = 0.0356, OR = 1.4, CI = 1.02–1.92) and rs11675434 in TPO gene ( p  = 0.041, OR = 1.31, CI = 1.01–1.69). Two of these SNPs (rs1077462, rs11675434) also showed association with TPOAb levels ( p  = 0.043, β  = −0.39; p  = 0.042, β  = 0.40, respectively) and one (rs7171171) was associated with thyroid gland volume ( p  = 0.0226, β  = −0.21). Our findings suggest that variants inside or near TPO, ATXN2 and RASGRP1 genes are associated with HT. Identified loci are novel to HT and represent good basis for further exploration of HT susceptibility.